Phosphorus status of some Ethiopian highland Vertisols - Mamo, T.; Haque, I.; Kamara, C.S. (International Livestock Centre for Africa, 1988)
Presents the results of investigations on the relative distribution of the various phosphorus forms, fixing capacity and status of some Ethiopian highland Vertisols.